2022
DOI: 10.14715/cmb/2021.67.5.3
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the alpha-glucosidase inhibitory potential of dietary phytochemicals against diabetes mellitus type 2 via molecular interactions and dynamics simulation

Abstract: The research aims to identify the inhibitory potential of natural dietary phytochemicals against non-insulinotropic target protein alpha-glucosidase and its possible implications to diabetes mellitus type 2.A data set of sixteen plant-derived dietary molecules viz., 4,5-dimethyl-3-hydroxy-2(5H)-furanone, apigenin, bromelain, caffeic acid, cholecalciferol, dihydrokaempferol 7-o-glucopyranoside, galactomannan, genkwanin, isoimperatorin, luteolin, luteolin 7-o-glucoside, neohesperidin, oleanoic acid, pelargonidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…18,19 We used redocking of (3 R ,5 R ,7 R )-octane-1,3,5,7-tetracarboxylic acid as the enzyme substrate. 20 The setup study was used to assess the reliability of the docking procedure. The result showed an root mean square deviation value of 1.23957 Å (<2 Å), indicating that the docking protocol is suitable for the current study as depicted in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 We used redocking of (3 R ,5 R ,7 R )-octane-1,3,5,7-tetracarboxylic acid as the enzyme substrate. 20 The setup study was used to assess the reliability of the docking procedure. The result showed an root mean square deviation value of 1.23957 Å (<2 Å), indicating that the docking protocol is suitable for the current study as depicted in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular nucleotide pyrophosphatase/phosphodiesterase family (E-NPPs) is widely involved in many regulatory processes, such as nucleotide cycle, pyrophosphate level regulation, phospholipid signaling regulation, cell movement stimulation, insulin receptor regulation, and activation of some extracellular kinases. Abnormal expression of E-NPPs was found in many diseases, such as bone mineralization disorder, abnormal cell movement and metastasis, angiogenesis, tumor invasion, type 2 diabetes, and others (14)(15)(16). A previous study found that NPP1 had the effect of anti-insulin and inhibited the phosphorylation of insulin receptors stimulated by insulin (17).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, only these ligands were taken forward for MD studies. [42][43][44][45] Vdw: Van der Waals, HB: Conventional Hydrogen Bond, CHB: Carbon Hydrogen Bond.…”
Section: Hydrogen Bond Analysismentioning
confidence: 99%